Transition Metal Complexes of Mn(II), Co(II) and zn(II) withTridentate Schiff Base and Neutral Monodentate Ligand - Parihari, R.K.; Patel, R.N. (Asian Journal of Chemistry, 2010)
Complexes of Mn(II), Co(II) and Zn(II) with tridentate Schiff base L = 2-hydroxy-1-naphthaldehyde semicarbazone (HNSC) and neutral ligand L´ = pyridine, isoquinoline, quinoline and γ-picoline with stoichiometry MLL´ (where M = Mn(II), Co(II), Zn(II), L and L´ = ligands) have been prepared and characterised by elemental analyses, molar conductance, molecular weight measurement, room temperature, magnetic susceptibility and infrared and electronic spectral measurements.